Clinical and angiographic features of young patients with myocardial infarction - Kalatsei, Liudmila V.; Rupasinghe, Dulki S. (International Journal of Research in Medical Sciences, 2026)
Background: Myocardial infarction (MI) is less common in young adults than in middle-aged and elderly people, but clinical interest to this problem is increasing due to the potential for premature death and long-term disability. Aim of the current study was to identify clinical, laboratory, and angiographic features of young (≤45 years) patients with MI. Methods: The study included 81 patients with acute MI who were divided into 2 age categories: 34 patients ≤45 years old (group 1), and 47 patients >45 years old (group 2). All patients underwent laboratory and instrumental studies, including coronary angiography. Statistical analysis was performed using STATISTICA 12.0. Results: The gender composition was represented predominantly by men (88% versus 81%, p>0.05). Young patients more often had ST-segment elevation on ECG (88%), while in older patients N-STEMI was more common (26% versus 12%, p=0.035). Younger patients had significantly higher troponin levels (p=0.028), indicating potentially greater myocardial injury. Angiographically, the incidence of single vessel disease was higher in patients below 45 years old (67.6 versus 29.7%, p<0.001). Conclusions: The study identified that risk factors for early development of MI include primarily male gender, smoking, obesity, and hypertension. Single-vessel lesions with the involvement of the left anterior descending artery were the most common angiographic finding. The ability to predict the risk of developing cardiovascular disease in young people opens new prospects for developing a strategic approach to the care of young people at elevated risk.